Application of V(Z) curve technique to study the elastic properties of various layers and detection of defects of a 3D wafer - Tan, Andrew Yong Sheng. (2011)
Electronic products are getting more compacted as technology of wafer fabrication advances. In addition, 3D wafer is seen by many as the next “popular technology” in the industry; due to its many advantages that this technology possesses. As new development progress, thinner layers are produced in the wafer. The details of wafer fabrication technology will not be discussed in this report, but the application of Non- Destructive Testing (NDT) on the 3D wafer examined. Characterising of elastic constant on a layered structure is desirable in some application. Thus, the elastic properties of the layers present in the 3D wafer are looked into by means of using V(z) technique which excite Rayleigh wave, that is closely related to the elastic constant of material. Conventional ultrasonic, utilising angle probe is also capable of exciting surface acoustic wave which directly measure the Rayleigh wave velocity. Ultra-thin layers are present in the 3D wafer; hence an investigation on the effects of surface wave on descending thickness of the specimen is carried out.